Intra-articular Alpha-2 Agonists as an Adjunct to Local Anesthetic in Knee Arthroscopy: A Systematic Review and Meta-Analysis - Ryan, Thomas James; Holyoak, Rhys; Vlok, Ruan; Melhuish, Thomas; Hodge, Anthony; Binks, Matthew; Hurtado, Glenn; White, Leigh (The Journal of Knee Surgery, 2019)
The infiltration of local anesthetic has been shown to reduce postoperative pain in knee arthroscopy. Several studies have shown that the addition of agents such as magnesium and nonsteroidal antiinflammatory drugs (NSAIDs) result in an increased time to first analgesia and overall reduction in pain. The aim of this systematic review and meta-analysis was to determine whether the addition of an α-2 agonist (A2A) to intra-articular local anesthetic, results in a reduction in postoperative pain. Four major databases were systematically searched for relevant randomized controlled trials (RCTs) up to July 2017. RCTs containing a control group receiving a local anesthetic and an intervention group receiving the same with the addition of an A2A were included in the review. The included studies were assessed for level of evidence and risk of bias. The data were then analyzed both qualitatively and where appropriate by meta-analysis. We reviewed 12 RCTs including 603 patients. We found that the addition of an A2A resulted in a significant reduction in postoperative pain up to 24 hours. The addition of the A2A increased time to first analgesia request by 258.85 minutes (p < 0.00001). Total 24-hour analgesia consumption was analyzed qualitatively with all included studies showing a significant reduction in total analgesia requirement. Interestingly, none of the studies found an increase in side effects associated with the A2A. This study provides strong evidence for the use of A2As as a means to reduce postoperative pain post arthroscopic knee surgery, without a corresponding increase in side effects.
Keywords: orthopaedic; arthroscopy; knee; local anesthetic; α agonist